THE EFFECT OF FINANCIAL ACCOUNTING SYSTEM AND PUBLIC SERVICE MOTIVATION ON THE LOCAL GOVERNMENT PERFORMANCE - Amir, Baso; Mediaty, Mediaty; Kusumawati, Andi; Darmawati, Darmawati (Equilibrium : Jurnal Ilmiah Ekonomi, Manajemen dan Akuntansi, 2024)
AbstractThis study aims to test and analyze the effect of regional financial accounting systems and public service motivation on local government performance. This study used primary data through survey method by distributing questionnaires to 40 SKPD within the scope of the Makassar city government. The entire population of this study was a research sample. The collected data was then analyzed using multiple linear regression analysis with the help of SPSS version 23. The results of this study show that the regional financial accounting system and public service motivation can have a positive and significant influence on the performance of local governments. The findings of this study indicate that the better the regional financial accounting system applied, the more understanding the PPK understands about the procedures, it will improve the performance of local governments, and the higher the motivation of public services possessed in each public sector employee, it will improve the performance of local governmentsKeywords: financial accounting system; public service motivation; local government performance. AbstrakPenelitian ini bertujuan untuk menguji dan menganalisis pengaruh sistem akuntansi keuangan daerah dan motivasi pelayanan publik terhadap kinerja pemerintah daerah. Penelitian ini menggunakan data primer melalui metode survei dengan menyebarkan kuesioner kepada 40 SKPD di lingkup pemerintah kota Makassar. Seluruh populasi dari penelitian ini menjadi sampel penelitian. Data yang terkumpul kemudian dianalisis dengan menggunakan analisis regresi linier berganda dengan bantuan SPSS versi 23. Hasil penelitian ini menunjukkan bahwa sistem akuntansi keuangan daerah dan motivasi pelayanan publik dapat memberikan pengaruh positif dan signifikan terhadap kinerja pemerintah daerah. Temuan penelitian ini menunjukkan bahwa semakin baik sistem akuntansi keuangan daerah yang diterapkan, semakin paham PPK tentang prosedur maka akan meningkatkan kinerja pemerintah daerah, dan semakin tinggi motivasi pelayanan publik yang dimiliki dalam diri setiap pegawai sektor publik maka akan meningkatkan kinerja pemerintah daerah.Kata kunci: sistem akuntansi keuangan; motivasi pelayanan publik; kinerja pemerintah daerah.